The application research of xTAG GPP multiplex PCR in the diagnosis of persistent and chronic diarrhea in children - Chunli Wang; Xiaoying Zhou; Mengshu Zhu; Hanjun Yin; Jiamei Tang; Yan Huang; Bixia Zheng; Yu Jin; Zhifeng Liu (BMC, 2020)
Abstract Background Persistent and chronic diarrhea is difficult to treat, and infection is still the main cause. In this study, we investigate the application value of xTAG gastrointestinal pathogen panel (xTAG GPP) multiplex PCR in the early diagnosis of persistent and chronic diarrhea in children and to understand the epidemiology of intestinal diarrhea pathogens. Methods One hundred ninety-nine specimens were collected from Nanjing Children's Hospital Affiliated to Nanjing Medical University (Nanjing, China). We compared the xTAG GPP multiplex PCR assay with traditional methods (culture, rapid enzyme immunoassay chromatography, and microscopic examination) and performed a statistical analysis. Results The positive rate of the xTAG GPP multiplex PCR assay of diarrhea specimens from 199 patients was 72.86% (145/199). The virus detection rate was 48.7%, and rotavirus A was the most common organism detected (34.67%), concentrated in winter, and was common in children. The second most common organism detected was norovirus GI/GII (20.6%). The positive rate of this bacteria was 40.2%, and Campylobacter (22.11%, 44/199) was most frequently detected. C. difficile toxins A/B and Salmonella was detected in 44 and 17 samples, respectively. Infections with Shigella occurred 4 times, and E. coli O157 was only detected once. Three samples were parasitic (1.51%), two samples were positive for Entamoeba histolytica, and one was positive for Cryptosporidium. Adenovirus 40/41, STEC, ETEC, Giardia, Yersinia enterocolitica and Vibrio cholerae were not detected. In total, 86 (43.2%) infected specimens with a single pathogen were detected. There were 59 coinfections (29.65% of the samples) of viruses and/or bacteria and/or parasites. Coinfections involved 49 double infections (24.62%), 9 triple infections (4.52%) and 1 quadruple infections (0.5%). Norovirus GI/GII was found to have the highest involvement, with 32 coinfections (16.08%). Conclusion The xTAG GPP multiplex PCR assay is simple, sensitive, and specific and can be used as a quick way to diagnose persistent and chronic diarrhea in children.